THE EFFECT OF DOPANT CONCENTRATION ON THE CRYSTAL STRUCTURE AND MAGNETIC PROPERTIES OF TIO₂ - Abdumannopova , Mukhlisaxon (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
In this article, the effect of dopant (especially Co, Mn, Fe) concentration on modifying the magnetic properties of TiO₂ semiconductor material was studied. Studies show that the amount of dopant has a significant effect on the crystal lattice parameters, phase state and ferromagnetic behavior. If at low concentrations a homogeneous DMS state is formed, at high concentrations secondary phases and clustering are observed.